A study of performance analysis of fan coil unit system for FKM's air conditioner - Nina Nadia, Sahim (2012)
Air conditioning system is a process of ventilation, air movement, air cleanliness, dehumidifying and cooling in order to give comfort to occupant. In tropical climate countries like Malaysia, air conditioner is very important to cool building space. Currently, most of commercial building in Malaysia is equipped with air conditioner either by using split unit or central unit types. Installation of air conditioner requires heat gain estimation, so that the capacity of the installed air conditioner is suitable for the particular area and gives the best performance in its operation. This project is carried out to determine the heat gain and analyze performance of air conditioner at second floor Block 2. FKM buildings start the operation in 2009. In 2009, every building in FKM building is window glass single glazing without tinted film. Started from year 2011, those windows glass have been tinted to reduce glare and heat gain inside the room. Besides that, factor of recommended setting temperature by Malaysia government at 24 Â°C also affected the design of air conditioning system. Generally, the main air conditioning system working at FKM is central air conditioning system. A method has been implemented to obtain the heat gain which is cooling load temperature difference/cooling load factor, (CLTD/CLF) while for cooling capacity, energy equation throughout fan coil has been used. The heat gain study have been considered five rooms in the second floor Block 2 (lecture rooms) which are Lecture Room 5 (BK 5), Lecture Room 6 (BK 6), Briefing Room 8 (BT 8), Briefing Room 6 and 7 (BT 6 and 7), and Discussion Room 6, 7 and 8 (BP 6, 7 and 8). From these five rooms, there are only two rooms have been analyze the performance which are Bilik Kuliah 5 and Bilik Taklimat 8. The study of heat gain is conducted from 8.00 am until 5.00 pm. The result shows that the heat gains are 14.43 kW, 14.31 kW, 8.35 kW, 15.61 kW and 7.3 kW, respectively. The percentage comparison heat gain against cooling coil load with load for Briefing Room 8 and Lecture Room 5 are 34.45 % and 47.98 % less than the heat gain by rooms. It happened because the data for cooling coil load were taken at steady state condition, while the heat gain data were measured in unsteady state condition. Thus, the fan coil still capable to cooled the rooms in steady state conditions.